3dways internationalization project: in-depth market analysis of Germany as a potential target market - SME competitiveness field lab 2019/2020 - Martins, Miguel Afonso Pereira (2020)
3DWays is a 3D printing service-providing company. Currently, the company wants to internationalize its remotely managed network of 3D printing factories, specifically targeting the health care sector. The refore, this project analyses the current and futures tate of the 3D Printing industry, before assessing potential target markets. Subsequently, five countries, head lined by the United Kingdom, were determined to be themost suitable for the company’s internationalization that willrely on direct exporting as an entry strategy because of the unique nature of the network. Complementary, a marketing plan and a financial evaluation were developed for 3DWays in the UK.